Analysis of compartmentalized cAMP: a method to compare signals from differently targeted FRET reporters. - Stangherlin, A; Koschinski, A; Terrin, A; Zoccarato, A; Jiang, H; Fields, L; Zaccolo, M (2014)
Förster resonance energy transfer (FRET)-based reporters are important tools to study the spatiotemporal compartmentalization of cyclic adenosine monophosphate (cAMP) in living cells. To increase the spatial resolution of cAMP detection, new reporters with specific intracellular targeting have been developed. Therefore it has become critical to be able to appropriately compare the signals revealed by the different sensors. Here we illustrate a protocol to calibrate the response detected by different targeted FRET reporters involving the generation of a dose-response curve to the cAMP raising agent forskolin. This method represents a general tool for the accurate analysis and interpretation of intracellular cAMP changes detected at the level of different subcellular compartments.